Behavior therapy as a theoretical approach to group counseling - Zola, Nilma; Suhaili, Neviyarni; Karneli, Yeni; Netrawati, Netrawati (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
Through group counseling, clients are given a safe and comfortable place to convey the problems they are experiencing so that they can help them in alleviating these problems. The problem will be discussed with other group members, who may also have the same problem. Counselors, as group leaders, can use various relevant approaches to realize the goals of group counseling, one of which is behavior therapy. Behavior therapy focuses on observable behaviors and learning experiences that promote change. The research approach employed is library research. We based the development of this manuscript on a survey of several publications from research articles in behavior therapy. The author used a thematic analysis to get basic conclusions concerning counselors’ use of behavior therapy as a theoretical approach to group counseling. We intend this paper to serve as a literature for counselors who desire to use a behavior therapy approach in group counseling.